'A tender gourd among the cactus'. Making sense of Myanmar's alignment policies through the lens of strategic culture. Issue 6 (1st November 2020) - Passeri, Andrea
Abstract: The article sheds light on a series of cognitive features and cultural determinants ingrained in the historical evolution of Myanmar's alignment choices vis-à-vis regional great-powers. Building upon Alastair Johnston's conceptualisation of 'strategic culture', the study traces the genesis, articulation, and perpetuation of a distinctive set of beliefs and assumptions embraced by different generations of Burmese decision-makers to cope with the country's security dilemma. Accordingly, Myanmar's hedging attitude in the midst of the ongoing Sino-American rivalry is presented as a further manifestation of its deep-rooted neutralist practice, which was firstly employed to navigate the perilous waters of the Cold War and then evolved into a crucial standard of conduct to safeguard a relative degree of autonomy in the shadow of a rising China.